Evaluation of gene markers invA, phsB, and tviA for detection of Salmonella Typhi by SYBR Green TM real-time PCR assay in clinical samples - Muhammad Luqman Qadir; Samreen Arshad; Nazim Hussain; Saima Younas; Rabia Arooj; Ahmer Bin Hafeez (Molecular Biology Reports, 2026)

Next-generation hybrid membranes integrating MXene and MOF architectures for energy-efficient water treatment - Saleem Raza; Luqman Ali; Muhammad Usman Hameed; Sidra Khalid; Sundas Shoukat; Mamuna Ahmad; Liguo Shen; Ghafar Ali; Imran Shakir (Desalination, 2026)

Recent advances in electrochemical ion separation: Materials, mechanisms and sustainable applications for water and resource recovery - Luqman Ali; Abdul Majid Khan; Muhammad Usman Hameed; Saleem Raza; Liguo Shen; Imran Shakir; Muhammad Hafeez (Desalination, 2026)

Phytochemical profiles and therapeutic potentials of Thalictrum species in Africa and Asia: a structured review with evidence quality assessment and strategic framework for drug discovery - Sagir Mustapha; Lukman Mustapha; Suciati Suciati; Kayatri Govindaraju; Irma Wati Ngadimon; Muhammad Luqman Nordin; Mustapha Mohammed; Hamza Lawal; Hasiya Usman Jibrilla; Nabil Abdulkarim; Ahmad Khusairi Azemi (Plant Biosystems, 2026)

Marine-derived natural products as adaptogens: Enhancing fish resilience to climate and environmental stressors - Ahmad Khusairi Azemi; Nor Hafizah Zakaria; Thirukanthan Chandra Segaran; Yik Sung Yeong; Mazlan Abd Ghaffar; Wong Li Lian; Muhammad Luqman Nordin; Tengku Sifzizul Tengku Muhammad (Regional Studies in Marine Science, 2026)

Methotrexate Loaded Polymeric Patches with Penetration Enhancers for Transdermal Delivery: in vitro, Ex Vivo, and in Vivo Characterization - Muhammad Shahid Latif; Asif Nawaz; Muhammad Khurshid Alam Shah; Muhammad Fareed; Muhammad Waseem Khan; Muhammad Luqman Nordin; Omar Awad Alsaidan; Sami I. Alzarea (Journal of Pharmaceutical Innovation, 2026)

Evaluation of Chitosan-Methotrexate Nanoparticles Loaded in Alginate Beads for Controlled Drug Delivery Against Breast Cancer - Abdullah Khan; Muhammad Fareed; Muhammad Khurshid Alam Shah; Asif Nawaz; Muhammad Faisal Shahzad; Muhammad Fauzi Abd Jalil; Zarif Mohamed Sofian; Muhammad Luqman Nordin (Journal of Pharmaceutical Innovation, 2026)

Advances in functional carbon composites for electrochemical energy conversion and catalysis: Design strategies, mechanisms and future prospects - Luqman Ali; Muhammad Usman Hameed; Xingfen Huang; Saleem Raza; Abdul Majid Khan; Mashkoor Ahmad; Akif Safeen; Imran Shakir (Journal of Environmental Chemical Engineering, 2026)

Antimicrobial Potential and Genomic Insights of Novel Klebsiella Phage SBP against K-112 Serotype - Muhammad Asif; Iqbal Ahmad Alvi; Sibgha; Muhammad Luqman Qadir; Shafiq-ur-Rehman (Current Microbiology, 2026)

Characterization and fungicidal sensitivity of Phytophthora species causing citrus gummosis in Pakistan - Hadeed Ahmad; Muhammad Wahab; Muhammad Atiq; Muhammad Usman; Muhammad Hamza Shahid; Muhammad Usman Ali; Owais Iqbal; Muhammad Luqman Aleem; Qurban Ali; Nasir Ahmed Rajput (Physiological and Molecular Plant Pathology, 2026)

Recent advances in vaccination strategies against acute hepatopancreatic necrosis disease (AHPND) in shrimp for sustainable aquaculture industry: A comprehensive review - Tijani Isa; Riyanto Teguh Widodo; Suzita Mohd Noor; Nur Asyura Nor Amdan; Zulhisyam Abdul Kari; Norhidayah Mohd Taufek; Fathiah Mohamed Zuki; Alias Abdullah; Subha Bhassu; Zarif Mohamed Sofian; Sagir Mustapha; Didi Erwandi Mohamad Haron; et al. (Fish & Shellfish Immunology, 2026)

Assessing the impact of nano-pollutants on the growth and development of stream breeding frogs - Isma Maqbool; Laraib Khadija; Muhammad Rais; Anila Rahim; Luqman; Muhammad Naveed Iqbal Raja; Zia-ur-Rehman Mashwani; Muhammad Shahbaz; Sumbul Gill; Muhammad Saeed (Biologia, 2026)

Enhancing permeance and antifouling properties of PVDF nanofiltration membranes using polydopamine grafted CuO@CeO2 photocatalyst composite for antibiotic wastewater treatment - Tutuk Djoko Kusworo; Andri Cahyo Kumoro; Luqman Buchori; Muhammad Daffa Alfarizi; Riska Dwi Amalia; Meitri Bella Puspa; Dani Puji Utomo; Tonni Agustiono Kurniawan; Febio Dalanta (Journal of Water Process Engineering, 2025)

Recent progress in biomass polymer based hydrogel membranes for adsorption and photocatalytic pollutants removal: fabrication, challenges and future perspectives - Muhammad Usman Hameed; Luqman Ali; Ayesha Ahmad; Pei Zhang; Saleem Raza; Sikandar Khan; Wei-Ren Liu; Zainab Amjad (Desalination, 2025)

Enhancement and evaluation of vardenafil hydrochloride trihydrate absorption in orodispersible tablet formulations: Establishment of in vitro, in vivo correlation and bioequivalence study - Kok Zheng Gan; Riyanto Teguh Widodo; Zamri Chik; Muhammad Luqman Nordin; Liew Kai Bin (Chemico-Biological Interactions, 2025)

Modulatory effects of phytoestrogens, fresh soy milk, and annexin A1 on cell cycle regulation and apoptotic pathways in human leukemic cells and peripheral blood mononuclear cells - Qalidah Mohamad Ali; Ahmad Khusairi Azemi; Siti Hawa Nordin; Sagir Mustapha; Muhammad Luqman Nordin (Biocatalysis and Agricultural Biotechnology, 2025)

Evaluating Tunnel Squeezing in the Lawi Hydropower Project, Chitral, Pakistan: Geological and Empirical Perspectives - Muhammad Tariq Niaz; Waqas Ahmed; Shah Faisal Khattak; Jehanzeb Khan; Luqman Ahmad; Ihtisham Islam; Salman Ahmed Khattak (Geotechnical and Geological Engineering, 2025)

Tropical-extratropical interactions: the atmospheric dynamics behind Dubai's extreme precipitation in April 2024 - Muhammad Latif; Muhammad Usman; Abdul Malik; Sateesh Masabathini; Burhan Ahmad; Luqman Atique; Fatima Alhammadi; Ibrahim Hoteit (Natural Hazards, 2025)

New insights on the potentiality of deep learning techniques in supporting the assessment of some biotic diseases on maize - Sajjad Hussain Qureshi; Sohail Raza Chohan; Muhammad Usman; Muhammad Luqman; Mueen Alam Khan; Baber Ali; Reem M. Aljowaie; Mohamed S. Elshikh; Rashid Iqbal (Journal of Plant Pathology, 2025)

Integrated landslide risk assessment utilizing open source satellite and ground data in the Himalayas of Northern Pakistan - Naseem Ahmad; Muhammad Shafique; Mian Luqman Hussain; Munawar Shah; Punyawi Jamjareegulgarn; Nassir Saad Alarifi; Mostafa R. Abukhadra (Natural Hazards, 2025)

Effect of Gracilaria changii extract and its fraction in reverse cholesterol transport by targeting SR-BI gene - Mohd Rahaizuddin Rani; Ahmad Khusairi Azemi; Kamariah Bakar; Luqman Abu-Bakar; Tengku Sifzizul Tengku Muhammad; Noraznawati Ismail (Natural Product Research, 2025)

Corrigendum to “Genetic parameters for resistance to field mortality outbreaks and resistance to a pathogenic strain of Vibrio splendidus in Mytilus edulis, Mytilus galloprovincialis and natural hybrid” [Aquaculture, Volume 590] - Munusamy Ajithkumar; Marie Lillehammer; Marie-Agnés Travers; Elise Maurouard; Muhammad Luqman Aslam; Lionel Dégremont (Aquaculture, 2025)

From bias to accuracy: Transforming satellite precipitation data in arid regions with machine learning and topographical insights - Faisal Baig; Luqman Ali; Muhammad Abrar Faiz; Haonan Chen; Mohsen Sherif (Journal of Hydrology, 2025)

Stability of five strains of PRRSV in tap water at different temperatures - Valeria Lugo-Mesa; Nader M. Sobhy; Muhammad Luqman; Christian D. Ramirez-Camba; Cesar A. Corzo; Sagar M. Goyal (Veterinary Microbiology, 2025)

Investigating the impact of inhomogeneous roughness on the drag of a planing craft assisted by numerical simulation - Muhammad Luqman Hakim; Ahmad Firdhaus; Samuel Samuel; Soonseok Song; Sanghyun Kim; I Ketut Aria Pria Utama (Ocean Engineering, 2025)

Prediction of the salmon lice density on wild sea trout from the mean predicted lice density in the sea: A cross-validation of the data in - Bjarne Gjerde; Muhammad Luqman Aslam (Aquaculture, 2025)

Recent advances in recycling and upcycling of hazardous plastic waste: A review - Siti Zulaika Khairul Anuar; Abu Hassan Nordin; Siti Muhamad Nur Husna; Abdul Hafidz Yusoff; Syafikah Huda Paiman; Siti Fadilla Md Noor; Muhammad Luqman Nordin; Siti Nurlia Ali; Ya Mohammad Nazir Syah Ismail (Journal of Environmental Management, 2025)

Recent progress in 2D-MXene-based membranes for water treatments; fabrication, properties, and advanced desalination application - Muhammad Usman Hameed; Zainab Amjad; Basem Al Alwan; Atef El Jery; Hassan M.A. Hassan; Luqman Ali; Ayesha Ahmad; Sikandar Khan; Saleem Raza (Desalination, 2025)

Integrated debris flow hazard and risk assessment using UAV data and RAMMS, a case study in northern Pakistan - Naseem Ahmad; Muhammad Shafique; Mian Luqman Hussain; Israr Ullah (Natural Hazards, 2025)

Natural resource abundance, digitalization and institutional governance: The critical challenges towards net-zero transformation - Muhammad Farhan Bashir; Madiha Bashir; Luqman Shahzad (Resources Policy, 2024)

Methodology comparison of environmental sediment fungal community analysis - Xinlei Li; Yongjie Li; Yingying Wang; Yanyan Liu; Luqman Riaz; Qingqing Wang; Xiangpeng Zeng; Zhao Qin; Muhammad Irfan; Qingxiang Yang (Environmental Research, 2024)

Sea level rise estimation and projection from long-term multi-mission satellite altimetry and tidal data in the Southeast Asia region - Muhammad Luqman Ahmad Affandi; Ami Hassan Md Din; Abd Wahid Rasib (International Journal of Remote Sensing, 2024)

Movement of amphibians in a habitat mosaic of agriculture landscape - Waseem Ahmed; Muhammad Rais; Ayesha Akram; Muhammad Saeed; Luqman; Sumbul Gill; Aamina Abid; Abdul Hadi (European Journal of Wildlife Research, 2024)

Genetic parameters for resistance to field mortality outbreaks and resistance to a pathogenic strain of Vibrio splendidus in Mytilus edulis, Mytilus galloprovincialis and natural hybrid - Munusamy Ajithkumar; Marie Lillehammer; Marie-Agnès Travers; Elise Maurouard; Muhammad Luqman Aslam; Lionel Dégremont (Aquaculture, 2024)

Effect of bacillus strain and Fe-modified biochar on lead (Pb) bioaccumulation and oxidative stress in wheat (Triticum aestivum L.) grown in Pb contaminated soil - Sana Noreen; Zaffar Malik; Muhammad Luqman; Ishrat Fatima; Usama Ali Tahir; Mansab Dar; Muhammad Rizwan (South African Journal of Botany, 2024)

Uptake, Agglomeration, and Detoxification of Trace Metals and Metalloids in Plants - Babar Hussain; Aqleem Abbas; Aansa Rukya Saleem; Luqman Riaz; Shafeeq Ur Rahman; Shibin Liu; Shengyan Pu; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2024)

Integrative taxonomy of the featherback fish genus Chitala (Osteoglossomorpha: Notopteridae) in Peninsular Malaysia - Luqman Hakim Ruzman; Jamsari Amirul Firdaus Jamaluddin; Abdullah Halim Muhammad‐Rasul; Tedjo Sukmono; Md. Zain Khaironizam; Sébastien Lavoué (Zoologica Scripta, 2024)
The taxonomy of the freshwater featherback fish genus Chitala (Osteoglossomorpha: Notopteridae) remains unsettled because delimiting and naming Chitala species based solely on morphology led to different hypotheses. In this study, we aim to determine the number and identity of Chitala species present in Peninsular Malaysia by employing an integrative taxonomic approach that combines morphology and two mitochondrial markers: the cytochrome c oxidase subunit I (COI) and cytochrome b genes. A total of 60 specimens of Chitala were collected throughout Peninsular Malaysia. Initially, all specimens were sorted into three distinct categories based on their body marking patterns. A molecular phylogenetic analysis revealed that each of these groups was monophyletic, and an automated species partition method further recognized them as distinct species. These results support the presence of three Chitala species in Peninsular Malaysia, even though a multivariate morphometric analysis failed to fully differentiate each of these three species. Comparison with original species descriptions and genetic data from an additional 70 Chitala specimens from neighbouring regions allowed us to name these species as Chitala lopis , Chitala borneensis , and Chitala ornata . We also showed the presence of two undescribed species in Indonesia.

Modern ecofriendly approach for extraction of luteolin natural dye from weld for silk fabric and wool yarn dyeing - Syed Ali Raza Naqvi; Kaif ul-Wara; Shahid Adeel; Rony Mia; Mozhgan Hosseinnezhad; Luqman Jameel Rather; Muhammad Imran (Sustainable Chemistry and Pharmacy, 2024)

Prediction of the impact of biofouling roughness on a full-scale planing boat performance using CFD - Wilma Amiruddin; Muhammad Luqman Hakim; Ahmad Firdhaus; Dian Purnamasari; Tuswan Tuswan; Samuel Samuel; Ocid Mursid (Ocean Engineering, 2024)

Economic complexity, greenfield investments, and energy innovation: policy implications for sustainable development goals in newly industrialised economies - Muhammad Farhan Bashir; Roula Inglesi-Lotz; Ummara Razi; Luqman Shahzad (Environmental Science and Pollution Research, 2024)

Transition towards natural resource rents and green technology to achieve China's COP26 success: A novel insights in the case of trade openness and environmental pollution - Muhammad Luqman (Resources Policy, 2024)

Explaining urban communities’ adaptation strategies for climate change risk: novel evidence from Rawalpindi, Pakistan - Naeem Ahmed; Muhammad Luqman (Natural Hazards, 2024)

Fintech, natural resource abundance, environmental regulations and energy consumption in BRICST and G7 economies: Empirical evidence from novel climate change index - Beiling Ma; Mehmet Akif Destek; Luqman Shahzad; Muhammad Farhan Bashir (Resources Policy, 2024)

How accurate are the machine learning models in improving monthly rainfall prediction in hyper arid environment? - Faisal Baig; Luqman Ali; Muhammad Abrar Faiz; Haonan Chen; Mohsen Sherif (Journal of Hydrology, 2024)

A wearable self-powered microneedle system based on conductive drugs for infected wound healing: A new electrical stimulation delivery strategy - Shanguo Zhang; Tianyi Jiang; Fang Han; Liangyu Cao; Ming Li; Zhenyou Ge; Haoxiu Sun; Hao Wu; Wenlong Wu; Nannan Zhou; Muhammad Luqman Akhtar; Hongyuan Jiang (Chemical Engineering Journal, 2024)

Abiogenic silicon: Interaction with potentially toxic elements and its ecological significance in soil and plant systems - Babar Hussain; Luqman Riaz; Kun Li; Kashif Hayat; Naveed Akbar; Muhammad Zakwan Hadeed; Bowei Zhu; Shengyan Pu (Environmental Pollution, 2023)

Genetic characterization of coarse and basmati rice (Oryza sativa L.) through microsatellite markers and morpho-agronomic traits - Tahira Luqman; Zia-ul Qamar; Aqsa Tabasum; Wael. H. El-Kallawy; Talha Nazir; Safira Attacha; Sajid Fiaz; Muhammad Azhar Nadeem; Amjad Hameed; Zahra Maryum; Itoh Kimiko; Kotb Attia (Genetic Resources and Crop Evolution, 2023)

Casting shadows on natural resource commodity markets: Unraveling the quantile dilemma of gold and crude oil prices - Muhammad Luqman; Adil Mugheri; Najid Ahmad; Ugur Soytas (Resources Policy, 2023)

Soil Erosion Estimation of Mohmand Dam Watershed Using Geo-spatial Techniques in KPK, Pakistan - Muhammad Imran; Muhammad Sanaullah; Usman Ahmad; Luqman Ahmed (Geotechnical and Geological Engineering, 2023)

Examining the role of ICT, transportation energy consumption, and urbanization in CO2 emissions in Asia: a threshold analysis - Zakia Batool; Naeem Ahmed; Muhammad Luqman (Environmental Science and Pollution Research, 2023)

Green surface functionalization of chitosan with spent tea waste extract for the development of an efficient adsorbent for aspirin removal - Abu Hassan Nordin; Norzita Ngadi; Rushdan Ahmad Ilyas; Nur Aien Fatini Abd Latif; Muhammad Luqman Nordin; Mohd Syahlan Mohd Syukri; Walid Nabgan; Syafikah Huda Paiman (Environmental Science and Pollution Research, 2023)

Cow bone-derived biochar enhances microbial biomass and alters bacterial community composition and diversity in a smelter contaminated soil - Muhammad Azeem; Parimala Gnana Soundari Arockiam Jeyasundar; Amjad Ali; Luqman Riaz; Khalid S. Khan; Qaiser Hussain; Hafiz A. Kareem; Fakhar Abbas; Abdul Latif; Ali Majrashi; Esmat F. Ali; Ronghua Li; et al. (Environmental Research, 2023)

Biomonitoring of mercury in water, sediments, and fish (brown and rainbow trout) from remote alpine lakes located in the Himalayas, Pakistan - Javed Nawab; Junaid Ghani; Syed Aziz Ur Rehman; Muhammad Idress; Muhammad Luqman; Sardar Khan; Ali Asghar; Ziaur Rahman (Environmental Science and Pollution Research, 2022)

Spatio-temporal landslide inventory and susceptibility assessment using Sentinel-2 in the Himalayan mountainous region of Pakistan - Alam Sher Bacha; Muhammad Shafique; Harald van der Werff; Mark van der Meijde; Mian Luqman Hussain; Sohail Wahid (Environmental Monitoring and Assessment, 2022)

Spatial source apportionment of pollution and health risks in the agricultural soils of Shangla, Northern Pakistan: multistatistical approach - Shah Jehan; Seema Anjum Khattak; Sardar Khan; Lixin Wang; Liaqat Ali; Muhammad Waqas; Mian Luqman Hussain (Arabian Journal of Geosciences, 2022)

An outlook on the development of renewable energy, policy measures to reshape the current energy mix, and how to achieve sustainable economic growth in the post COVID-19 era - Muhammad Farhan Bashir; Muhammad Sadiq; Besma Talbi; Luqman Shahzad; Muhammad Adnan Bashir (Environmental Science and Pollution Research, 2022)

Phyto-mediated photocatalysis: a critical review of in-depth base to reactive radical generation for erythromycin degradation - Aniqa Ashraf; Guijian Liu; Balal Yousaf; Muhammad Arif; Rafay Ahmed; Audil Rashid; Luqman Riaz; Muhammad Saqib Rashid (Environmental Science and Pollution Research, 2022)

Quantile nexus between human development, energy production, and economic growth: the role of corruption in the case of Pakistan - Muhammad Luqman; Yafei Li; Salah Ud-Din Khan; Najid Ahmad (Environmental Science and Pollution Research, 2021)

A bibliometric analysis and systematic literature review of tourism-environmental degradation nexus - Muhammad Shahbaz; Muhammad Farhan Bashir; Muhammad Adnan Bashir; Luqman Shahzad (Environmental Science and Pollution Research, 2021)

Landslide assessment by using multi-temporal UAV datasets: a case study in northern Pakistan - Naseem Ahmad; Muhammad Shafique; Mian Luqman Hussain (Arabian Journal of Geosciences, 2021)

Genome-wide molecular characterization of Phosphate Transporter 1 and Phosphate Starvation Response gene families in Elaeis guineensis Jacq. and their transcriptional response under different levels of phosphate starvation - Muhammad Luqman Hamzah; Siti Nor Akmar Abdullah; Azzreena Mohamad Azzeme (Acta Physiologiae Plantarum, 2021)

Correction to: Elucidating the distinct interactive impact of cadmium and nickel on growth, photosynthesis, metal-homeostasis, and yield responses of mung bean (Vigna radiata L.) varieties - Muhammad Aqeel; Noreen Khalid; Aasma Tufail; Rana Zaheer Ahmad; Muhammad Salim Akhter; Muhammad Luqman; Muhammad Tariq Javed; Muhammad Kashif Irshad; Saad Alamri; Mohamed Hashem; Ali Noman (Environmental Science and Pollution Research, 2021)

Elucidating the distinct interactive impact of cadmium and nickel on growth, photosynthesis, metal-homeostasis, and yield responses of mung bean (Vigna radiata L.) varieties - Muhammad Aqeel; Noreen Khalid; Aasma Tufail; Rana Zaheer Ahmad; Muhammad Salim Akhter; Muhammad Luqman; Muhammad Tariq Javed; Muhammad Kashif Irshad; Saad Alamri; Mohamed Hashem; Ali Noman (Environmental Science and Pollution Research, 2021)

Scientific data-driven evaluation of academic publications on environmental Kuznets curve - Muhammad Farhan Bashir; Benjiang Ma; Muhammad Adnan Bashir; Bilal; Luqman Shahzad (Environmental Science and Pollution Research, 2021)

Role of silicon on root morphological characters of wheat (Triticum aestivum L.) plants grown under Cd-contaminated nutrient solution - Shafeeq Ur Rahman; Qi Xuebin; Ghulam Yasin; Hefa Cheng; Faisal Mehmood; Muhammad Zain; Muhammad Shehzad; Muhammad Irfan Ahmad; Luqman Riaz; Abdur Rahim; Saeed Ur Rahman (Acta Physiologiae Plantarum, 2021)

Landslide inventory and susceptibility assessment using multiple statistical approaches along the Karakoram highway, northern Pakistan - Mian Luqman Hussain; Muhammad Shafique; Alam Sher Bacha; Xiao-qing Chen; Hua-yong Chen (Journal of Mountain Science, 2021)

A brief review of socio-economic and environmental impact of Covid-19 - Muhammad Farhan Bashir; Benjiang MA; Luqman Shahzad (Air Quality, Atmosphere & Health, 2020)

Evaluation of rapid polymyxin Nordmann Poirel test for detection of polymyxin resistance in clinical isolates of Enterobacteriaceae - Muhammad Shoaib; Ashfaq Hussain; Luqman Satti; Wajid Hussain; Gohar Zaman; Faisal Hanif (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Biodegradation of Poly(3-hydroxybutyrate) and Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) by Newly Isolated Penicillium oxalicum SS2 in Soil Microcosms and Partial Characterization of Extracellular Depolymerase - Sadia Mehmood Satti; Ziaullah Shah; Aaisha Luqman; Fariha Hasan; Muhammad Osman; Aamer Ali Shah (Current Microbiology, 2020)

Microzonation map of the Abbottabad basin and immediate surroundings - Sarfraz Khan; Muhammad Waseem; Muhammad Asif Khan; Zahid Hussain; Waqas Ahmed; Ahmad Hamad Khaliq; Nisar Bin Umair; Mian Luqman Hussain (Journal of Seismology, 2020)

Human health risks by potentially toxic metals in drinking water along the Hattar Industrial Estate, Pakistan - Shah Jehan; Seema Anjum Khattak; Said Muhammad; Liaqat Ali; Abdur Rashid; Mian Luqman Hussain (Environmental Science and Pollution Research, 2020)

Sharing the costs and benefits of climate change mitigation via Shapley value - Muhammad Luqman; Ugur Soytas; Sui Peng; Shaoan Huang (Environmental Science and Pollution Research, 2019)

Geology as a proxy for Vs30-based seismic site characterization, a case study of northern Pakistan - Muhammad Shafique; Mian Luqman Hussain; M. Asif Khan; Mark van der Meijde; Sarfraz Khan (Arabian Journal of Geosciences, 2018)

Ag-loaded thermo-sensitive composite microgels for enhanced catalytic reduction of methylene blue - Luqman Ali Shah; Murtaza Sayed; Muhammad Fayaz; Irum Bibi; Mohsan Nawaz; Mohammad Siddiq (Nanotechnology for Environmental Engineering, 2017)

Missense mutations (p.H371Y, p.D438Y) in gene CHEK2 are associated with breast cancer risk in women of Balochistan origin - Abdul Hameed Baloch; Shakeela Daud; Nafeesa Raheem; Muhammad Luqman; Adeel Ahmad; Abdul Rehman; Jameela Shuja; Saeeda Rasheed; Akhtar Ali; Naseebullah Kakar; Hafiz Khush Naseeb; Mohammad Alam Mengal; et al. (Molecular Biology Reports, 2014)